Multi-objective optimization of turning parameters for targeting surface roughness and maximizing material removal rate in dry turning of AISI 316L with PVD-coated cermet insert - Touggui, Youssef; Belhadi, Salim; Mechraoui, Salah-Eddine; Uysal, Alper; Yallese, Mohammed Athmane; Temmar, Mustapha (SPRINGER INTERNATIONAL PUBLISHING AG, 2020)
The intention of investigating the alternative cutting tool performance, namely cermet insert to support the usage of coated cemented carbide for enhancing the productivity in turning of hard to cut materials such as stainless steels, is the rationality of this research.Therefore, the aim of this study is to determine the influence of cutting parameters such as cutting speed, feed and depth of cut on surface roughness (Ra) and material removal rate (MRR) during dry turning of AISI 316L using cermet insert (GC1525). Experimental tests were carried out according to Taguchi L-27 orthogonal array. The technique of response surface methodology and analysis of variance were also used to develop the quadratic regression model. Four optimization cases were performed using the desirability function to find the optimal cutting parameters by targeting Ra and maximizing MRR, unlike other researches that have focused only on minimizing Ra. Based on the results, it was found that the most predominant parameter affecting the Ra was the feed with 79.61% of contribution, while the MRR was strongly influenced by the depth of cut followed by cutting speed and feed, respectively. Tool wear tests were also performed and the results indicated that the tool life of cermet tool was measured as 30 min at cutting speed of 340 m/min.
Keywords: Machining; Austenitic stainless steel; Cermet; RSM; ANOVA; Desirability function; STAINLESS-STEEL; CUTTING PARAMETERS; POWER-CONSUMPTION; MACHINING PARAMETERS; TAGUCHI DESIGN; FLANK WEAR; PERFORMANCE; MQL; MACHINABILITY; Science & Technology - Other Topics